A preparation process of modified PVDF coating for building walls

Through the preparation of nano-modified particles and high-temperature and high-pressure reaction technology, the PVDF resin formula and preparation process were optimized, and a modified PVDF coating was developed, which solved the problem of VOC emission and construction difficulty in traditional PVDF coatings during construction, and achieved the improvement of the high mechanical strength, weather resistance and environmental protection performance of the coating.

CN119410211BActive Publication Date: 2025-04-04INNER MONGOLIA WANHAO FLUOROCHEM +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510018221.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing PVDF coatings release volatile organic compounds (VOCs) during production and construction, which poses a threat to the environment and the health of construction personnel. At the same time, the curing temperature of powder coatings is high and the construction is difficult, which limits its application range.

Method used

Through the preparation of nanomodified particles and high-temperature and high-pressure reaction technology, the PVDF resin formulation and preparation process are optimized to develop a modified PVDF coating. The nano-modified particles are prepared by the coordinated reaction of sodium carbonate, methyl trimethoxysilane and ammonia in anhydrous ethanol. They have small particle size, high specific surface area and surface functionalization characteristics, which significantly improve the mechanical strength and weather resistance of the coating.

Benefits of technology

Modified PVDF coatings significantly reduce VOC emissions, improve the mechanical strength, weather resistance and chemical corrosion resistance of the coating, enhance adhesion and self-cleaning capabilities, meet high-performance needs such as building walls, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410211B_ABST
    Figure CN119410211B_ABST
Patent Text Reader

Abstract

The present invention discloses a process for preparing a modified PVDF coating for use on building walls, and relates to the technical field of polymer modified materials. The process significantly improves the weather resistance, chemical corrosion resistance, mechanical strength and long-term stability of the PVDF coating by introducing nano-modified particles and performing high-temperature and high-pressure reactions. Specifically, the process comprises: (1) preparing nano-modified particles, and (2) mixing the nano-modified particles, titanium dioxide, epoxy resin emulsion and vinylidene fluoride monomer, and performing high-temperature and high-pressure reactions to obtain modified PVDF powder. The coating preparation process is environmentally friendly and has excellent performance, is suitable for building wall decoration, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer modified materials, in particular to a preparation process of a modified PVDF coating applied to building walls. Background Art

[0002] PVDF (polyvinylidene fluoride) coating is a high-performance fluorinated polymer coating widely used in the construction field, with excellent weather resistance, chemical corrosion resistance, mechanical strength and long-term stability. Its core characteristics come from the super strong CF bond and regular arrangement of fluorinated groups in the PVDF molecular structure, which makes the coating show excellent durability and anti-aging ability in harsh environments such as ultraviolet rays and acid rain.

[0003] Traditional PVDF coatings are mainly solvent-based. Although they have excellent performance, they release volatile organic compounds (VOCs) during production and construction, posing a threat to the environment and the health of construction workers. In addition, although powder coatings have overcome the VOC emission problem, their high curing temperature and difficulty in construction also limit their scope of application.

[0004] In recent years, in order to meet the growing environmental protection and performance requirements, water-based PVDF coatings have gradually become a research hotspot. By blending PVDF with acrylic resin and introducing functional additives, the adhesion, film-forming properties and environmental characteristics of the coating can be significantly improved. However, the current water-based PVDF coatings still have room for improvement in coating process optimization and comprehensive performance improvement.

[0005] In addition, the development of polymer material modification technology provides more possibilities for optimizing the performance of PVDF coatings. For example, through nanomaterial enhancement, blending modification and surface modification, its wear resistance, self-cleaning ability and adhesion can be further improved to meet higher-end architectural decoration needs. Summary of the invention

[0006] The present invention aims to develop a modified PVDF coating which has excellent comprehensive performance, is environmentally friendly and is suitable for building walls by improving the PVDF resin formula and preparation process, so as to solve the problems existing in the prior art and broaden its application scope.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: A process for preparing a modified PVDF coating for use on building walls, comprising the following steps: (1) Preparation of nano-modified particles: firstly, 4 to 8 parts by weight of sodium carbonate and 1 to 3 parts by weight of methyltrimethoxysilane are dispersed in 25 to 35 parts by weight of anhydrous ethanol to obtain a dispersion, 20 to 30 parts by weight of ammonia water are added to the dispersion at a rate of 1 part by weight / min under magnetic stirring, the dispersion is placed in an oil bath at 50°C to 70°C for 2h to 3h, and then shaken for 12h, and the nano-modified particles are obtained by filtering and drying;

[0008] The first step involves the preparation of nano-modified particles, which are generated by the reaction of sodium carbonate, methyltrimethoxysilane and ammonia in anhydrous ethanol. This process involves a variety of chemical reactions and physical processes, and the final product plays a key role in optimizing the performance of the coating.

[0009] As a weak alkaline substance, sodium carbonate mainly plays the role of adjusting the pH value in the reaction system, providing a suitable alkaline environment for the hydrolysis and polycondensation of methyltrimethoxysilane (MTMS). Its particle size is precisely controlled to ensure uniform dispersion and sufficient reaction. In addition, sodium carbonate weakly interacts with some hydrolysis products during the reaction, further stabilizing the structure of the nanoparticles.

[0010] Methyltrimethoxysilane (MTMS) is a siloxane precursor with three hydrolyzable methoxy groups and one hydrophobic methyl group. In anhydrous ethanol solvent and alkaline conditions, MTMS first undergoes partial hydrolysis to generate silanol (Si-OH) intermediates; then, the generated silanol molecules form silicon-oxygen bonds (Si-O-Si) through polycondensation reactions, gradually constructing nanoparticles with a three-dimensional network structure.

[0011] Ammonia plays a dual role in the reaction system: Catalyst: Ammonia provides a strong alkaline environment, accelerates the hydrolysis and polycondensation reaction of MTMS, and improves the particle generation efficiency. Morphology regulator: Ammonia molecules coordinate with silanols or intermediates to regulate the nucleation and growth process of nanoparticles, ensuring uniform particle size and stable distribution.

[0012] Anhydrous ethanol is not only a good solvent, but also acts as a dispersion medium in the whole process. It can effectively reduce the viscosity of the system, promote the uniform dispersion of reactants, and avoid particle agglomeration.

[0013] The nano-modified particles prepared by the above chemical reaction and physical process have the following remarkable characteristics: Small and uniform particle size: By precisely controlling the reaction conditions, the size of the nanoparticles can be stabilized in the range of 10-100 nm. This small and uniform particle size helps to improve the performance of the coating. High specific surface area: The nano-scale size brings a large specific surface area, allowing the particles to fully contact with other components in the coating matrix and improve the interfacial bonding force. Surface functionalization: Since the methyl groups in the MTMS molecule do not participate in the polycondensation reaction, these organic functional groups remain on the surface of the particles, providing them with a certain degree of hydrophobicity and enhancing the compatibility with PVDF resin and epoxy resin emulsion. Stable network structure: Through the cross-linking of silicon oxygen bonds (Si-O-Si), a highly stable and dense three-dimensional network structure is formed, which makes the nanoparticles have good mechanical strength and thermal stability. After the nano-modified particles are introduced into the PVDF coating as fillers, they form a composite material together with the resin matrix. Its high specific surface area and network structure can effectively fill the micropores inside the coating and reduce the defect area, thereby significantly improving the mechanical strength of the coating. In addition, the high bond energy of the silicon-oxygen bond (about 451 kJ / mol) gives the coating higher impact resistance and wear resistance. The silicon-oxygen bond has strong resistance to ultraviolet radiation, so the nano-modified particles can significantly improve the weather resistance of the coating in outdoor environments. The test results show that after the introduction of nano-modified particles, the thermal decomposition temperature of the coating is increased to above 580°C, which greatly delays the aging process. The nano-modified particles form a dense barrier in the coating, effectively blocking the penetration of corrosive media (such as water, oxygen, acid and alkali solutions). The organic functional groups on the surface of the nano-modified particles can interact with the active groups in the PVDF resin and epoxy resin emulsion to improve the interfacial bonding force. At the same time, these functional groups also promote the uniform distribution of the coating during film formation, making the coating denser and smoother, thereby improving adhesion and reducing the risk of shedding. Due to the presence of hydrophobic methyl groups on the surface of the nano-modified particles, the modified PVDF coating exhibits a lower surface energy, making it difficult for dirt and water droplets to adhere, thus having excellent self-cleaning ability. This feature is particularly important for building wall applications and can effectively reduce maintenance costs. This step adopts the sol-gel method to prepare nano-modified particles, which has the following advantages: Controllable process: By adjusting the rate of ammonia addition, oil bath temperature and stirring speed, the particle size and morphology can be precisely controlled. Environmentally friendly and efficient: non-toxic and harmless reagents such as anhydrous ethanol are used as solvents, which greatly reduces the emission of volatile organic compounds (VOCs). Suitable for large-scale production: The process is simple and easy to operate, and the raw materials are cheap and easy to obtain, which provides convenient conditions for industrial production. In the first step, nano-modified particles with excellent functions were successfully prepared by the synergistic reaction of sodium carbonate, MTMS and ammonia in anhydrous ethanol. These particles play a key role in optimizing the performance of PVDF coatings with their small and uniform size, high specific surface area, surface functionalization and stable network structure.They significantly improve the mechanical strength, weather resistance, corrosion resistance, self-cleaning ability and adhesion of the coating, providing a high-performance solution for the field of building wall decoration while showing good industrialization potential.

[0014] (2) Preparation of modified PVDF: First, 0.5 parts by weight of nano-modified particles, 1 to 6 parts by weight of titanium dioxide, 30 to 40 parts by weight of epoxy resin emulsion and 30 to 50 parts by weight of vinylidene fluoride monomer are mixed, and the mixing temperature is controlled at 80°C to 90°C. Then, 1 to 3 times the weight of pure water and 0.1 times the weight of perfluorohexanoic acid are added to the mixed solution, and a high-temperature and high-pressure reaction is carried out to obtain a reactant. Then, the reactant is dried in a vacuum drying oven to obtain a powder.

[0015] Vinylidene fluoride (PVDF) monomers undergo free radical polymerization under high temperature and pressure conditions to produce linear or partially branched PVDF polymers. The reaction uses perfluorohexanoic acid (PFA) as an emulsifier and dispersant to provide a stable emulsion system and promote the uniform dispersion of the monomers. The polymerization process forms a highly crystalline PVDF matrix, and the strong polar CF bonds in its molecular structure give the material excellent chemical corrosion resistance and thermal stability. The nano-modified particles undergo physical adsorption or chemical bonding with the PVDF segments through surface functional groups (such as Si-OH or Si-CH3), forming strong interfacial interactions. This interfacial bonding not only improves the dispersibility of the nanoparticles in the matrix, but also enhances the mechanical strength and thermal stability of the composite material.

[0016] Titanium dioxide, which has abundant hydroxyl groups on its surface, can interact with polar groups (such as hydroxyl and epoxy groups) in PVDF or epoxy resin. The main functions of titanium dioxide in the system include: Photocatalytic activity: after absorbing ultraviolet light, it generates active oxygen species, which gives the coating antibacterial and self-cleaning capabilities. Shielding effect: The particles form a physical barrier in the coating, effectively blocking ultraviolet rays and water penetration, and improving the weather resistance of the coating. The epoxy groups in the epoxy resin emulsion undergo cross-linking reactions with the active functional groups on the surface of the PVDF segments or nanoparticles under high temperature and high pressure conditions to form a dense three-dimensional network structure. This cross-linking reaction significantly improves the mechanical properties, adhesion and corrosion resistance of the composite material.

[0017] Nano-modified particles form a strong interface bond with the PVDF matrix through their high specific surface area and surface functional groups. The specific functions include: providing additional mechanical reinforcement effect, improving the hardness and toughness of the coating. Reducing the extension of microcracks through uniform dispersion, improving the impact resistance of the coating. Strengthening the adhesion between the coating and the substrate. Titanium dioxide, as a functional filler, not only improves the weather resistance of the coating, but also gives it self-cleaning properties: Titanium dioxide has a strong ability to absorb ultraviolet rays, which can effectively delay the aging of the coating. The surface hydroxyl groups form hydrogen bonds with other components, improving the overall stability of the composite material.

[0018] As a binder and toughening agent, epoxy resin emulsion plays the following key roles in the system: It improves the film-forming properties of the coating, making it denser and smoother. It enhances the overall strength of the coating through cross-linking reactions, while improving chemical corrosion resistance. It provides excellent adhesion, allowing the coating to firmly adhere to substrates such as building walls.

[0019] Vinylidene fluoride monomer is the main film-forming substance of the whole system. The PVDF segments generated by its polymerization give the coating the following characteristics: excellent weather resistance, which can resist environmental erosion such as ultraviolet rays and acid rain for a long time. Excellent chemical corrosion resistance, suitable for various harsh environments. Good thermal stability, so that the coating can withstand high temperatures without degradation.

[0020] As an emulsifier, PFA plays the following roles in the preparation process: stabilizing the emulsion system and preventing the components from agglomerating. Providing a good dispersion effect, the nanoparticles and titanium dioxide are evenly distributed in the PVDF matrix. The nanoparticles and epoxy resin together construct a dense network structure, which greatly improves the mechanical strength and toughness of the composite material. The test results show that the coating exhibits higher impact resistance and wear resistance, which can effectively extend the service life. Titanium dioxide and PVDF segments together give the coating excellent UV resistance, allowing it to be exposed to the outdoor environment for a long time without losing gloss or powdering. In addition, titanium dioxide also reduces water vapor and oxygen penetration through shielding, improving the stability of the coating. The epoxy resin emulsion and nanoparticles work together to form a dense barrier in the coating, effectively blocking the intrusion of corrosive media (such as acid, alkali, and salt solutions). Cross-linking reaction occurs between epoxy resin and PVDF segments, and nanoparticles fill micropores, greatly improving the bonding between the coating and the substrate. This strong adhesion makes the coating show better anti-peeling ability in building wall applications. Due to the photocatalytic activity of the titanium dioxide surface and the hydrophobic properties of the nanoparticle surface, the modified PVDF coating exhibits excellent self-cleaning capabilities. Water droplets form a balling effect on its surface, which can carry away dust and dirt, thereby reducing maintenance costs.

[0021] The present invention successfully prepares a modified PVDF powder with excellent comprehensive performance by synergistically mixing nano-modified particles, titanium dioxide, epoxy resin emulsion and vinylidene fluoride monomer, and performing polymerization and cross-linking reactions under high temperature and high pressure conditions. The final product not only has excellent mechanical strength, weather resistance and corrosion resistance, but also exhibits good adhesion, self-cleaning properties and environmental advantages, providing a new efficient and reliable solution for building wall and other fields.

[0022] Preferably, the particle size of the sodium carbonate in step (1) is 50 um-100 um.

[0023] The rotation speed of the magnetic stirring in step (1) is 120 r / min.

[0024] The concentration of ammonia water in step (1) is 100 mg / mL.

[0025] Preferably, the rotation speed of the shaking table in step (1) is 60 r / min.

[0026] The pore size of the filter in step (1) is 0.22 μm.

[0027] The drying method in step (1) is vacuum drying.

[0028] The drying temperature in step (1) is 40°C-60°C.

[0029] Preferably, the particle size of titanium dioxide in step (2) is 0.1 um-0.2 um.

[0030] The parameters of the epoxy resin emulsion in step (2) are as follows: the epoxy resin solid content is 60% by mass, the viscosity is 820mPa·s, the epoxy resin particle diameter is 0.4um, and the pH value is 8.5. The type of epoxy resin is epoxy resin E-20. The preparation method of the above-mentioned epoxy resin emulsion is as follows: the ethylene glycol monoethyl ether solution containing epoxy resin E-20 (the mass ratio of epoxy resin E-20 to ethylene glycol monoethyl ether is 1:2) and the emulsifier polyetheramine D230 are stirred and mixed uniformly at a mass ratio of 100:7, and distilled water is slowly added and diluted until the solid content of the epoxy resin is 60% by mass and the viscosity is 820mPa·s, and the pH value is adjusted to 8.5.

[0031] Preferably, the parameters of the vinylidene fluoride monomer in step (2) are as follows: CAS number: 75-38-7, molecular weight: 64.04 g / mol.

[0032] The conditions of high temperature and high pressure reaction in step (2) are as follows: 120°C-135°C, 10 bar-50 bar, 3 h-4 h.

[0033] Preferably, the drying temperature of the vacuum drying oven in step (2) is 80°C-95°C, and the moisture content after drying is controlled within 0.5%.

[0034] Preferably, the particle size of the powder in step (2) is 0.2 um-0.6 um.

[0035] Beneficial Effects

[0036] The present invention discloses a preparation process of a modified PVDF coating applied to building walls. By introducing nano-modified particles and optimizing the preparation process, a significant improvement on the traditional PVDF coating is achieved, and the following beneficial effects are achieved:

[0037] (1) Improved environmental performance

[0038] Reduced VOC emissions: Traditional solvent-based PVDF coatings release a large amount of volatile organic compounds (VOCs) during production and construction, posing a threat to the environment and the health of construction workers. The present invention uses a water-based system and nanomaterials to effectively reduce VOC emissions, meet current environmental protection requirements, and reduce environmental pollution.

[0039] Improved resource utilization: The introduction of nano-modified particles reduces the amount of solvent used in the coating, increases the solid content of the coating, reduces resource consumption, and complies with the concept of sustainable development.

[0040] (2) Performance optimization

[0041] Improved weather resistance: The introduction of nano-modified particles significantly improves the durability and anti-aging ability of the coating in harsh environments such as UV resistance and acid rain resistance. Through testing, the thermal decomposition temperature of the modified PVDF coating is increased to above 580°C, which is much higher than that of traditional PVDF coating, indicating that its stability at high temperatures has been significantly improved.

[0042] Improved chemical corrosion resistance: The modified PVDF coating showed excellent corrosion resistance in the corrosion behavior test. Through the Tafel polarization curve measurement, the polarization resistance (Rp) of the modified coating reached 91 KΩ·cm², the corrosion rate (CRRate) was only 0.04 mpy, the corrosion current density (i_corr) was reduced to 0.55 µA / cm², and the anti-corrosion efficiency (η) was as high as 94.8%. These data show that the protective performance of the modified PVDF coating in a chemically corrosive environment has been greatly improved.

[0043] Enhanced mechanical strength: The introduction of nano-modified particles enhances the mechanical strength of the coating, improves the wear resistance and scratch resistance of the coating, and extends the service life of the coating.

[0044] Improved adhesion and film-forming properties: Through the synergistic effect with epoxy resin emulsion and vinylidene fluoride monomer, the adhesion and film-forming properties of modified PVDF coatings are significantly improved, ensuring good bonding between the coating and the substrate and reducing the risk of coating shedding.

[0045] (3) Wide range of applications

[0046] Application on building walls: Modified PVDF coatings are suitable for scenes with high durability requirements such as building walls. Through the simulation of corrosion resistance test of architectural aluminum profile surface coating, modified PVDF coatings show excellent corrosion resistance, meeting the demand for high-performance coatings in the field of architectural decoration.

[0047] Diversified applications: In addition to building walls, modified PVDF coatings can also be used in other fields that require high weather resistance and corrosion resistance, such as outdoor billboards, bridges, ships, etc., broadening its application scope.

[0048] (4) Preparation process optimization

[0049] Process stability: The preparation process provided by the present invention has good stability and repeatability. Improved production efficiency: The optimized preparation process reduces the steps and time in the production process, improves production efficiency, and reduces production costs.

[0050] (5) Economic benefits

[0051] Cost control: Although the introduction of nano-modified particles increases the cost of raw materials, by optimizing the preparation process and improving the performance of the coating, the frequency of coating maintenance and replacement is reduced, the long-term use cost is reduced, and economic benefits are achieved.

[0052] Market competitiveness: The improved performance and environmental friendliness of modified PVDF coatings make them more competitive in the market and meet consumers' demand for high-performance, environmentally friendly coatings.

[0053] (6) Technological innovation

[0054] Application of nanomaterials: The present invention optimizes the performance of traditional PVDF coatings by introducing nanomaterials, reflects the development direction of polymer material modification technology, and promotes technological progress in the coatings industry.

[0055] Process innovation: The optimized preparation process not only improves the performance of the coating, but also provides new ideas and methods for the modification of other polymer materials, and has broad technical promotion value.

[0056] In summary, the modified PVDF coating preparation process provided by the present invention achieves a comprehensive improvement in coating performance through the introduction of nano-modified particles and the optimization of the preparation process, meets the demand for high-performance, environmentally friendly coatings in the field of architectural decoration, and has significant beneficial effects and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a sample picture of the coating solution prepared in Example 3 of the present invention.

[0058] Figure 2 This is a scanning electron microscope image of the nano-modified particles prepared in Example 3 of the present invention.

[0059] Figure 3 This is the infrared spectrum of the coating solution prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0060] Example 1

[0061] The preparation process of modified PVDF coating applied to building walls comprises the following steps: (1) preparation of nano-modified particles: firstly, 4 kg of sodium carbonate and 3 kg of methyltrimethoxysilane are dispersed in 25 kg of anhydrous ethanol to obtain a dispersion liquid, 20 kg of ammonia water is added to the dispersion liquid at a rate of 1 kg / min under magnetic stirring, oil bathed at 50°C for 3 hours, and then shaken for 12 hours, and nano-modified particles are obtained by filtering and drying; the particle size of sodium carbonate in step (1) is 50 μm; the speed of magnetic stirring in step (1) is 120 r / min; the concentration of ammonia water in step (1) is 100 mg / mL. The speed of shaking table treatment in step (1) is 60 r / min; the pore size of filtration in step (1) is 0.22 μm; the drying method in step (1) is vacuum drying; and the drying temperature in step (1) is 40°C.

[0062] (2) Preparation of modified PVDF: First, 0.5 kg of nano-modified particles, 1 kg of titanium dioxide, 40 kg of epoxy resin emulsion and 30 kg of vinylidene fluoride monomer are mixed, and the mixing temperature is controlled at 80 ° C. Then, the mixed solution is added with 1 times the mass of pure water and 0.1 times the mass of perfluorohexanoic acid, and a high temperature and high pressure reaction is carried out to obtain a reactant. Then, it is dried in a vacuum drying oven to obtain a powder. The particle size of titanium dioxide in step (2) is 0.1 um; the parameters of the epoxy resin emulsion in step (2) are as follows: the solid content of epoxy resin is 60% by mass, the viscosity is 820 mPa·s, the diameter of epoxy resin particles is 0.4 um, and the pH value is 8.5. The parameters of the vinylidene fluoride monomer in step (2) are as follows: CAS number: 75-38-7, molecular weight: 64.04 g / mol; the conditions of the high temperature and high pressure reaction in step (2) are as follows: 120 ° C, 50 bar, 3 h. The drying temperature of the vacuum drying oven in step (2) is 80° C., and the moisture content after drying is controlled within 0.5%. The particle size of the powder in step (2) is 0.2 μm.

[0063] Example 2

[0064] The preparation process of modified PVDF coating applied to building walls comprises the following steps: (1) preparation of nano-modified particles: firstly, 8 kg of sodium carbonate and 1 kg of methyltrimethoxysilane are dispersed in 35 kg of anhydrous ethanol to obtain a dispersion liquid, 30 kg of ammonia water is added to the dispersion liquid at a rate of 1 kg / min under magnetic stirring, oil bathed at 70°C for 2 hours, and then shaken for 12 hours, and nano-modified particles are obtained by filtering and drying; the particle size of sodium carbonate in step (1) is 100 um; the speed of magnetic stirring in step (1) is 120 r / min; the concentration of ammonia water in step (1) is 100 mg / mL. The speed of shaking table treatment in step (1) is 60 r / min; the pore size of filtration in step (1) is 0.22 um; the drying method in step (1) is vacuum drying; and the drying temperature in step (1) is 60°C.

[0065] (2) Preparation of modified PVDF: First, 0.5 kg of nano-modified particles, 6 kg of titanium dioxide, 30 kg of epoxy resin emulsion and 50 kg of vinylidene fluoride monomer are mixed, and the mixing temperature is controlled at 90 ° C. Then, the mixed solution is added with 1 times the mass of pure water and 0.1 times the mass of perfluorohexanoic acid, and a high temperature and high pressure reaction is carried out to obtain a reactant. Then, it is dried in a vacuum drying oven to obtain a powder. The particle size of titanium dioxide in step (2) is 0.2 um; the parameters of the epoxy resin emulsion in step (2) are as follows: the solid content of epoxy resin is 60% by mass, the viscosity is 820 mPa·s, the diameter of epoxy resin particles is 0.4 um, and the pH value is 8.5. The parameters of the vinylidene fluoride monomer in step (2) are as follows: CAS number: 75-38-7, molecular weight: 64.04 g / mol; the conditions of the high temperature and high pressure reaction in step (2) are as follows: 135 ° C, 10 bar, 4 h. The drying temperature of the vacuum drying oven in step (2) is 95° C., and the moisture content after drying is controlled within 0.5%. The particle size of the powder in step (2) is 0.6 μm.

[0066] Example 3

[0067] The preparation process of modified PVDF coating applied to building walls comprises the following steps: (1) preparation of nano-modified particles: first, 6 kg of sodium carbonate and 2 kg of methyltrimethoxysilane are dispersed in 30 kg of anhydrous ethanol to obtain a dispersion, 25 kg of ammonia water is added to the dispersion at a rate of 1 kg / min under magnetic stirring, and the dispersion is subjected to an oil bath at 60°C for 2.5 hours, and then subjected to a shaking table treatment for 12 hours, and the nano-modified particles are obtained by filtering and drying; the particle size of the sodium carbonate in step (1) is 100 um; the speed of the magnetic stirring in step (1) is 120 r / min; the concentration of the ammonia water in step (1) is 100 mg / mL. The speed of the shaking table treatment in step (1) is 60 r / min; the pore size of the filtration in step (1) is 0.22 um; the drying method in step (1) is vacuum drying; and the drying temperature in step (1) is 50°C.

[0068] (2) Preparation of modified PVDF: First, 0.5 kg of nano-modified particles, 4 kg of titanium dioxide, 35 kg of epoxy resin emulsion and 40 kg of vinylidene fluoride monomer are mixed, and the mixing temperature is controlled at 85 ° C. Then, the mixed solution is added with 2 times the mass of pure water and 0.1 times the mass of perfluorohexanoic acid, and a high temperature and high pressure reaction is carried out to obtain a reactant. Then, it is dried in a vacuum drying oven to obtain a powder. The particle size of titanium dioxide in step (2) is 0.1 um; the parameters of the epoxy resin emulsion in step (2) are as follows: the solid content of epoxy resin is 60% by mass, the viscosity is 820 mPa·s, the diameter of epoxy resin particles is 0.4 um, and the pH value is 8.5. The parameters of the vinylidene fluoride monomer in step (2) are as follows: CAS number: 75-38-7, molecular weight: 64.04 g / mol; the conditions of the high temperature and high pressure reaction in step (2) are as follows: 128 ° C, 40 bar, 3.5 h. The drying temperature of the vacuum drying oven in step (2) is 88°C, and the moisture content after drying is controlled within 0.5%. The particle size of the powder in step (2) is 0.4 um.

[0069] Comparative Example

[0070] The preparation process of PVDF coating applied to building walls comprises the following steps: firstly, 4 kg of titanium dioxide, 35 kg of epoxy resin emulsion and 40 kg of vinylidene fluoride monomer are mixed, and the mixing temperature is controlled at 85°C, then the mixed solution is added with 2 times of pure water and 0.1 times of perfluorohexanoic acid, and a high temperature and high pressure reaction is carried out to obtain a reactant, and then the reaction is dried in a vacuum drying oven to obtain a powder. The particle size of titanium dioxide in step (2) is 0.1 um; the parameters of the epoxy resin emulsion in step (2) are as follows: the solid content of epoxy resin is 60% by mass, the viscosity is 820 mPa·s, the diameter of epoxy resin particles is 0.4 um, and the pH value is 8.5. The parameters of the vinylidene fluoride monomer in step (2) are as follows: CAS number: 75-38-7, molecular weight: 64.04 g / mol; the conditions of the high temperature and high pressure reaction in step (2) are as follows: 128°C, 40 bar, 3.5 h. The drying temperature of the vacuum drying oven in step (2) is 88°C, and the moisture content after drying is controlled within 0.5%. The particle size of the powder in step (2) is 0.4 um.

[0071] Test scheme: The coating powders prepared in Examples 1 to 3 were subsequently subjected to quality inspection, as shown in Table 1 below:

[0072] Table 1 Quality Inspection Report

[0073]

[0074] The coating powder prepared in Example 3 and the comparative example was added with distilled water, wherein the mass of the distilled water was twice that of the coating powder, and then heated to 55°C and stirred continuously (60 rpm) for 2 hours to obtain a coating solution for standby use. The coating solution prepared in Example 3 was as follows: Figure 1 As shown, the nano-modified particles prepared at the same time are Figure 2 As shown, and the infrared analysis results of the coating solution are as follows Figure 3 shown.

[0075] Next, the coating solution (Examples 1-3 and Comparative Example) was sprayed on a polished architectural aluminum substrate at 100°C using an air spray gun to simulate the corrosion resistance of the surface coating of the architectural aluminum profile. The spraying pressure was 6 bar, the spraying distance was 250 mm, the spraying voltage was controlled at 90 KV, and the spraying thickness was 100 um. Referring to the disclosed prior art method (https: / / doi.org / 10.3390 / coatings13101729), the Tafel polarization curve was measured to study the corrosion behavior of the surface coating and the aluminum substrate, and the results are shown in Table 2 below.

[0076] Table 2 Corrosion behavior results

[0077]

[0078] In general, for the quality inspection report provided in Table 1: the coating powders of Examples 1-3 are all white powders without agglomeration, indicating that there is no significant difference in the appearance of the preparation process. The relative density of all examples is 1.76 g / cm³, indicating that the density of the modified PVDF coating remains consistent. The melting temperatures of Examples 1-3 are 182.4°C, 182.7°C and 183.2°C, respectively, which is related to the introduction of nano-modified particles, which enhances the thermal stability of the coating. The thermal decomposition temperatures of Examples 1-3 are 580.2°C, 581.1°C and 584.2°C, respectively, indicating that the stability of the modified PVDF coating at high temperatures has been improved. Compared with the corrosion behavior result table provided in Table 2, the anode Tafel slopes (βa) of Examples 1-3 are 527 mV, 530 mV and 531 mV, respectively, which are significantly higher than 387 mV of the comparative example, indicating that the modified PVDF coating exhibits higher electrochemical stability in the anode reaction. The cathode Tafel slopes (βc) of Examples 1-3 are 296 mV, 301 mV, and 308 mV, respectively, which are also higher than 194 mV of the comparative example, indicating that the modified PVDF coating also exhibits better corrosion resistance in the cathode reaction. The polarization resistance (Rp) of Examples 1-3 is 87 KΩ·cm², 89 KΩ·cm², and 91 KΩ·cm², respectively, which is much higher than 49 KΩ·cm² of the comparative example, indicating that the corrosion resistance of the modified PVDF coating is significantly improved. The corrosion rate (CR Rate) of Examples 1-3 is 0.04 mpy, while that of the comparative example is 0.06 mpy, indicating that the corrosion rate of the modified PVDF coating is reduced by about 33%. The corrosion current density (i_corr) of Examples 1-3 is 0.60 µA / cm², 0.58 µA / cm² and 0.55 µA / cm², respectively, which is significantly lower than 1.28 µA / cm² of the comparative example, indicating that the corrosion current density of the modified PVDF coating is reduced by about 57%. The anticorrosion efficiency (η) of Examples 1-3 is 94.5%, 94.7% and 94.8%, respectively, which is higher than 88.7% of the comparative example, indicating that the anticorrosion effect of the modified PVDF coating is significantly improved.

[0079] In summary, the present invention has successfully developed a modified PVDF coating with excellent comprehensive performance, environmental protection and suitable for building walls by introducing nano-modified particles and optimizing the preparation process. Compared with traditional PVDF coatings, the modified coating has significantly improved weather resistance, chemical corrosion resistance, mechanical strength and long-term stability, meeting the demand for high-performance coatings in the field of architectural decoration.

[0080] The above describes in detail the preferred implementation of this patent, but this patent is not limited to the above implementation. Various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of this patent.

Claims

1. A process for preparing a modified PVDF coating for use on building walls, characterized in that: The steps include: (1) Preparation of nano-modified particles: First, 4 to 8 parts by weight of sodium carbonate and 1 to 3 parts by weight of methyltrimethoxysilane are dispersed in 25 to 35 parts by weight of anhydrous ethanol to obtain a dispersion, 20 to 30 parts by weight of aqueous ammonia are added to the dispersion at a rate of 1 part by weight / min under magnetic stirring, an oil bath at 50° C. to 70° C. is placed for 2 h to 3 h, and a shaking table is then performed for 12 h, and nano-modified particles are obtained by filtering and drying; (2) Preparation of modified PVDF: First, 0.5 parts by weight of nano-modified particles, 1 to 6 parts by weight of titanium dioxide, 30 to 40 parts by weight of epoxy resin emulsion and 30 to 50 parts by weight of vinylidene fluoride monomer are mixed, and the mixing temperature is controlled at 80°C to 90°C. Then, 1 to 3 times the mass of pure water and 0.1 times the mass of perfluorohexanoic acid are added to the mixed solution to carry out a high-temperature and high-pressure reaction to obtain a reactant. Then, a vacuum drying oven is used to dry the reactant to obtain a powder.

2. The modified PVDF coating preparation process for building wall according to claim 1, characterized in that: The particle size of the sodium carbonate in step (1) is 50 um-100 um; The speed of magnetic stirring in step (1) is 120 r / min; The concentration of ammonia water in step (1) is 100 mg / mL.

3. The modified PVDF coating preparation process for building wall according to claim 2, characterized in that: The rotation speed of the shaking table in step (1) is 60 r / min; The pore size of the filter in step (1) is 0.22 μm; The drying method in step (1) is vacuum drying; The drying temperature in step (1) is 40°C-60°C.

4. The process for preparing the modified PVDF coating for use on building walls according to claim 3, characterized in that: The particle size of titanium dioxide in step (2) is 0.1um-0.2um; The parameters of the epoxy resin emulsion in step (2) are as follows: The solid content of the epoxy resin is 60% by mass, the viscosity is 820 mPa·s, the diameter of the epoxy resin particles is 0.4 um, and the pH value is 8.

5.

5. The process for preparing the modified PVDF coating for use on building walls according to claim 4, characterized in that: The parameters of the vinylidene fluoride monomer in step (2) are as follows: CAS number: 75-38-7, molecular weight: 64.04 g / mol; The conditions of the high temperature and high pressure reaction in step (2) are as follows: 120℃-135℃, 10bar-50bar, 3h-4h.

6. The process for preparing the modified PVDF coating for use on building walls according to claim 5, characterized in that: In step (2), the drying temperature of the vacuum drying oven is 80°C-95°C, and the moisture content after drying is controlled within 0.5%.

7. The process for preparing the modified PVDF coating for use on building walls according to claim 6, characterized in that: The particle size of the powder in step (2) is 0.2um-0.6um.

Citation Information

Patent Citations

  • Fluororesin composition, coating, printed circuit board, dielectric material for substrate, laminated circuit board, sheet, and method for producing fluororesin composition

    JP2024102462A

  • A coating composition manufacturing method of silica aerogel for radon mitigation

    KR102040964B1